ABDALS of ANAMUR: A COMMUNITY EXCLUDED WITH REGARD to ITS LANGUAGE, BELIEF and IDENTITY - Nas, Gönül Erdem (My University, 2018)
The Abdals are people who live in the centre of Anamur, especiallyin Yeşilyurt and Yıldırım Beyazıt quarters.There are many different views about the origin of Abdal identity. Whilesome of Abdals claim that their ancestors migrated from Khorasan, someothers believe that they are Copts. The common idea is that the Abdals donot represent themselves as Turkish.Abdals claim that they are excluded by local people due to their physiologicalappearance and belief (Alewi). By the way they mention that there is no anyrelation between them and the other Alewi group known as Tahtacılar livingin Kaşdişlen village. They say that in context of belief, they are completelydifferent from each other.The data of the study is obtained by interviews with certain people. In depthinterviews were conducted with elderly people and generally with thosewho are uneducated. After the speeches were transcribed, it was found thatthe dialect spoken by Abdals has many things in common as well as manydifferences.The special language, beliefs and identity of Abdals of Anamur as an innercommunity have not been studied before, so it is believed that the study willhave a contribution to such literature.
Keywords: Folklor; Etnik Çalışmalar; Antropoloji